Evaluation instruments for primary care network structures: an integrative review - Lima, Maria Alice Dias da Silva (2019)
The study aimed to identify available instruments in the literature to evaluate the structure of primary health network in health systems. An integrated review of literature was carried out in health sciences, education, and management Databases, as follows: Medical Literature Analysis and Retrieval System Online (Medline), including the Cochrane Library, Embase, PsycINFO, Cumulative Index to Nursing and Allied Health Literature (CINAHL), ABI Inform, Latin American and Caribbean on Health Sciences Literature (Lilacs), and the Business Source Complete (Ebsco). Manuscripts published in English and Portuguese from 1995 to 2019 were included. The final sample contained nine articles, in which eight instruments were identified. They had as a common feature the approach on longitudinality, interprofessional communication, care coordination, access to health services, and quality of care. An emphasis was noted on an instrument developed in the Brazilian health system context as a useful tool to support health care workers and managers in the situational diagnosis of potentialities and fragilities of Primary Health Care and Health Care Networks.